Peran Artificial Intelligence (AI) dalam Proses Pengambilan Keputusan terhadap Kinerja Organisasi: Analisis SLR - Hendrian Hendrian; Dedi Purwana; Saparuddin Saparuddin; Puji Wahono (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
The purpose of this research is to analyze the role of AI in decision-making on organizational performance. The method used is qualitative with secondary data. The data used is metadata on documents found on the Scopus website. The data was analyzed by the SLR method. The results of this study show that AI can help identify potential solutions by predicting the problems being studied by testing various variables and conditions in the simulation of organizational activities. AI can also improve performance through integration in decision-making.  However, not all roles performed by humans should be handled by AI, such as customer service. The use of AI agents as public service operators compared to human operators has a negative impact on the perception of the mutuality of public control in the organization-public relationship